Analisis Kesulitan Belajar Siswa dalam Membaca dan Menulis Al-Qur’an pada Pembelajaran Pendidikan Agama Islam Kelas VIII di SMP Negeri 3 Stabat - Regita, Selvi; Ginting, Nurman (Yayasan Rahmat Islamiyah, 2024)
The mission of this ponder is to expound and analyze course VIII understudies at SMP Negeri 3 Stabat who have trouble learning to examined and compose the Al-Qur’an amid Islamic devout instruction lessons.This ponder employments a expressive subjective strategy. Information collection through perceptions, tests, interviews and documentation. Miles and Huberman's intuitively examination was utilized for information appraisal. A Triangulation approach is utilized to guarantee the genuineness of the information. The subjects of the consider were the central, Islamic devout instruction educator and course VIII understudies of SMP Negeri 3 Stabat. The comes about of the think about appear that a few understudies don't involvement troubles and others do. Trouble perusing the Al-Qur’an, such as trouble proceeding the letters Hijaiyyah, floundered when presenting the verse, and didn't know it however Tajwid. Trouble in composing the Al-Qur’an, such as trouble composing a few letters Hijaiyyah, not composing accentuation accurately, and not being flawless in composing. The inside component is seldom presenting the Al-Qur’an. Outside components are restricted parental consideration, the impacts of the companionship environment and social media. The principal's activities incorporate making the classroom, supplication room, school field an region for examining the Al-Qur’an and holding morning proficiency each friday. The teacher's activities incorporate giving instruction on perusing and composing the Al-Qur’an within the classroom, supplication room and school field and empowering understudies to think about harder at domestic with their guardians or the closest Al-Qur’an instructor.